2011
DOI: 10.1016/j.physbeh.2010.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone is essential for cocaine sensitization in male rats

Abstract: Most studies agree that males and females respond differently to drugs of abuse. In females, estradiol enhances the behavioral response to cocaine. However, studies on the role of testosterone and the locomotor response to psychostimulants in the male rat are inconclusive. Our study was designed to determine the behavioral effects of testosterone on the development and persistence of cocaine sensitization in male rats. We tested different doses of cocaine (10, 15 and 30mg/kg) to determine which dose induced lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 74 publications
4
24
2
Order By: Relevance
“…Other studies have reported increased cocaine-induced locomotor activity and striatal dopamine in CAST male rats relative to intact rats (Camp & Robinson, 1988a, b; Hernandez et al, 1994; Purvis-Tyson et al, 2014; Robinson, 1984). In contrast, Menendez-Delmestre and Segarra (2011) observed cocaine-induced sensitization at 15 and 30 mg/kg in intact and CAST male rats with testosterone replacement but not in CAST male rats. Thus, it is difficult to decipher the role of testosterone on cocaine-induced locomotor based on the current literature.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Other studies have reported increased cocaine-induced locomotor activity and striatal dopamine in CAST male rats relative to intact rats (Camp & Robinson, 1988a, b; Hernandez et al, 1994; Purvis-Tyson et al, 2014; Robinson, 1984). In contrast, Menendez-Delmestre and Segarra (2011) observed cocaine-induced sensitization at 15 and 30 mg/kg in intact and CAST male rats with testosterone replacement but not in CAST male rats. Thus, it is difficult to decipher the role of testosterone on cocaine-induced locomotor based on the current literature.…”
Section: Introductionmentioning
confidence: 58%
“…Similar to the current experiment, Martinez-Sanchis et al (2002) did not find an effect of testosterone at doses greater than 10 mg/kg cocaine. Furthermore, Menendez-Delmestre and Segarra (2011) found that 15 and 30 mg/kg of cocaine progressively increased locomotor activity in intact and CAST male rats with testosterone replacement but not in CAST male rats. In contrast, several studies examining the role of testosterone in the behavioral effects of cocaine have failed to find differences between castrated (CAST) and intact male rodents (Becker et al, 2001; Forgie & Stewart, 1994; Hu & Becker, 2003; Hu et al, 2004; Robinson et al, 1981; van Haaren & Meyer, 1991).…”
Section: Discussionmentioning
confidence: 94%
“…Sex differences have been reported for sensitization to psychostimulants in rodents, which is likely related to augmented DA responses [249,250], with females showing a higher level of sensitization than males. E2 increases sensitization in OVX females [251-253], whereas the effects of CAST and T replacement are more variable [249,252,254-256]. We are unaware of any studies investigating sex differences in tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, estradiol facilitates positive subjective effects of drugs, while progesterone and its metabolite allopregnanolone attenuate drug-related responses and protect against the aversive effect of drugs in females (Becker et al , 2012; Carroll and Anker, 2010). Similarly, testosterone has been shown to modulate drug-related awarding effects and behavioral response differently in males and females (Menendez-Delmestre and Segarra, 2011; Bawor et al , 2014). …”
Section: Introductionmentioning
confidence: 99%